Front cover: Sesamol supplementation prevents systemic inflammation‐induced memory impairment and amyloidogenesis via inhibition of nuclear factor kappaB. Issue 5 (3rd May 2017) - Liu, Zhigang; Chen, Yuwei; Qiao, Qinglian; Sun, Yali; Liu, Qian; Ren, Bo; Liu, Xuebo
Abstract : Mol. Nutr. Food Res . 2017, 61, 1600734. DOI:10.1002/mnfr.201600734 Dietary supplementation of sesamol, a phenolic nutraceutical component from sesame, suppresses systemic‐inflammation‐induced memory impairment via binding with nuclear translocation and the DNA binding site of NFκB, and consequently blocking the activation of astrocyte/microglia and β‐amyloid accumulation.